GAMBARAN LITERASI MEDIA MAYA DALAM AKTIVITAS KESEHARIAN SISWA SEKOLAH MENENGAH KEJURUAN (SMK) DI KABUPATEN BANYUASIN (STUDI KASUS DI SMKN 1 SUAK TAPEH dan SMKN UNGGUL BANYUASIN) - Nopilda, Lisa (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is to find out the daily activities of Vocational High School students in Banyuasin District in conducting virtual media literacy activities (Case Study in SMK 1 of Suak Tapeh and Superior Banyuasin Vocational High School). The purpose of this study is to make a daily picture of students 'activities in conducting cyber literacy, all related actors / parties to describe students' daily activities. The research method used is Soft System Dynamic Methodology (SSDM), which is a combination of System Methodology (SSM) and Dynamic System (SD). Respondents were determined by purposive sampling method. Data were analyzed using a destructive approach. The results of the study revealed that student activities in everyday life use very little internet media which includes useful cyber literacy activities. The internet is only used to look for fun and friendship on social media. Gathering with friends adds to activities that are far from the expected cyber literacy activities.